ANALISIS DIMENSI KUALITAS PELAYANAN TERHADAP KEPUASAAN PASIEN PADA RSUD SYEKH YUSUF SUNGGUMINASA KABUPATEN GOWA - Asdi, Asdi (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2017)
Service quality is assessment base for impatient obtains health service activities at hospital. This research aim (1) how know the applying of dimension service quality consisted by tangible, empathy, reliability, responsiveness, and assurance has relationship with satisfaction of patient, and (2) dimension quality of which service gives the relation of dominance to satisfaction of patient. This research executed in Syekh Yusuf Public Hospital Sungguminasa Gowa Sub-Province, by getting sample 300 patient as responder. Data collecting using questionnaire and data processing applies analytical technique Chi-Square, Coefficient Contingence, and index of relation power. Result of research indicates that (1) either in simultan and also partially dimension service quality consisted of by tangible, empathy, reliability, responsiveness, and assurance has the relation of signifikan with satisfaction of patient, and (2) evidence dimension physical having the dominance relation to satisfaction of patient.